Factors influencing millennial choice of fast food at East Coast of Malaysia / Nur Fazlin Pakhri and Norazleena Mohd Zubri - Pakhri, Nur Fazlin; Mohd Zubri, Norazleena (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2017)
The objective of the study is to differentiate between males and females in East Coast of Malaysia pattern of menu choices at Fast Food. The main purpose is to identify the factors that influence millennial in choosing fast food at East Coast of Malaysia which including the factors which are price, location of restaurant, brand image of restaurant and taste of food. The survey was distributed to all millennial from East Coast of Malaysia Kelantan, Pahang and Terengganu. The respondents of this study were from 18 to 29 years old and this important information was highlighted when the researcher distributed the questionnaire. The questionnaire was distributed via Facebook and WhatsApp application because the researcher thought most of the millennial were the user for these applications. There is significant difference showed in the objective because of the factors of choosing fast food like price, location, taste, and brand. Most of the respondents chose to strongly disagree with the factors of choosing fast food that were listed. For the second objective, there was no significant difference showed because there were many females who responded to this questionnaire than the male which 79.7% of the respondents were female. This indicated that female respondents were more likely to buy fast food.